The lucky bilingual: ethnography of factors influencing code-switching among the Nubian community in southern Egypt - Tomoum, Syonara (AUC Knowledge Fountain, 2014)
The sociolinguistic aspect of code-switching has received attention of many scholars in the field of linguistics. This study builds on previous research and investigates the factors influencing code-switching amongst a bilingual Arabic and Nubian community of Nubians in Southern Egypt. Using Grosjean's (1982) model of factors influencing language choice, factors causing Nubian-Arabic bilinguals to speak one language over the other are investigated. Rouchdi (1991) suggested that Nubians are going through a language shift from Nubian to Arabic although she did not address the phenomenon of code-switching; this study looked at code-switching as an important factor in the language's tenuous survival as newer generations becoming increasingly Arabic monolingual. The factors influencing language choice determine what language will be used as a base language in any given interaction and the extent to which code-switching to the second language will occur. The study employed an ethnographic approach, where a triangulation of qualitative and quantitative instruments was used for maximum reliability and validity; methods used include observation, interviews, and questionnaires. Results were then cross-checked with Nubian cultural experts for additional validation. The study found that domain, or content of discourse, is a primary factor in determining language choice. It was also found that age plays a central role with fluency in Nubian (and therefore use) increasing in direct correlation with age. Last, but not least, it was found that Nubians, though fond of the Nubian language and proud of their heritage, exhibit a clear belief that Arabic is the language that will bring socioeconomic opportunity along with a belief that proficiency in Nubian is detrimental to mastery of the Arabic language. It is clear to Nubians that Arabic is the language that offers social, cultural, and economic capital as per Bourdieu (1977). Bourdieu suggested that a minority community would shift to the majority's language in exchange for better education, economic opportunity, and access to social networks. In line with this, many Nubian parents in recent generations have explicitly raised their children in Arabic-only environments. The study's discussion and conclusion present some practical suggestions as to how the Nubian language can survive despite its tenuous position amongst the youngest generations of speakers.